Managers` perceptions of a total package compensation system. - Rodgers, Clinton Bruce (My University, 2014)
The changing business environment in South Africa has resulted in significant organisational change taking place, as South African companies attempt to remain competitive in an increasingly globalised economy. A key feature in this change process is the way in which managers are remunerated, with a number of companies implementing a total package approach to managerial compensation. The purpose of this study was to exa 'nine management perceptions of a total package system, in terms of the fairness, equity and efficacy of the system. The research took the form of a case study in one large organisation, using a sample of 162 respondents. A questionnaire was used as the data collection tool, and the outcomes were analysed using the Spearman’s rank correlation co-efficient and interpretations! analysis. The analysis was then discussed in terms of the established theory base. Several factors that predicted perceptions of fairness, equity and efficacy of a total package remuneration system were derived from the analysis. These were consolidated into a process model for use by executives and compensation professionals in designing and implementing total package compensation systems. The model will facilitate the alignment of managerial effort behind organisational objectives, ensuring synergy between the compensation system and the achievement of strategic business objectives.